Basic Home Automation Using Smart Sockets with Power Management - Noufal, Asif; Yi Lung, Then; Jubaer, Ahmed; Saad, Kashem (Penerbit UTHM, 2021)
The power generated in today’s time is dominated using fossil fuels that may get exhausted within the coming decades. Monitoring and management of the energy consumption hold a prime standing due to the discrepancy between power demand and production. Power meters are a part of every household, which provides us with a measurement of the overall power consumed in units. The problem with them is that they do not provide us with the individual consumption of an electrical appliance leaving customers unsatisfied with the electricity bills. This paper presents the design and application of a smart power management system (SPMS) using a variety of sensors combined with an Arduino microcontroller. This will be replacing conventional home sockets with smart sockets, allowing us to cover the monitoring, control and safety aspects of any individual appliance in the house. This system is based on a newly evolving field worldwide, called the Internet of Things (IoT). The SPMS will be measuring the current, voltage, power factor and power consumed. Along with these measurements, it can also control the power state of the device and help protect against overvoltage and overcurrent. This is basically a home automation system, in combination with smart power management, all controlled and monitored by our smartphones. The edge this device has over conventional energy monitoring systems is that it allows the user to have an exact idea of individual power consumption plus the billing on a daily basis and take measures to reduce it.